Blessing in disguise; a case of Hereditary Persistence of Fetal Hemoglobin - Irfan Shaukat; Amrit Paudel; Sayf Yassin; Naseruddin Höti; Sadaf Mustafa (Greater Baltimore Medical Center, 2018)
Fetal Hemoglobin (HbF, α2γ2) is produced from the eighth week of gestation, constitutes 60 - 80 % of total hemoglobin by birth, which is then replaced with adult Hemoglobin A1 (HbA1: α2β2) by 6-12 months. Hereditary Persistence of Fetal Hemoglobin (HPFH) is a rare benign asymptomatic genetic disorder where the HbF persists, and incidentally discovered on screening for other hemoglobinopathies. In adults, the variation in HbF levels could also be associated with other disease states, including hemoglobinopathies, leukemias and bone marrow failure syndromes. Here we present a case of a young asymptomatic female with the incidental finding of HPFH who was misdiagnosed as the sickle cell disease. It is important to have awareness about HPFH and should be distinguished from other causes of elevated HbF.